2008
DOI: 10.1007/s11483-008-9094-3
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Induced Formation of β-Lactoglobulin Fibrils by AspN Endoproteinase

Abstract: This paper describes a low temperature, enzymatic route to induce fibrillar structures in a protein solution. The route comprises two steps. First, β-lactoglobulin was hydrolyzed into peptides at pH 8 and 37°C with the enzyme AspN endoproteinase, which resulted in the formation of random aggregates. After hydrolysis, the pH was lowered to 2. As a result, long fibrillar aggregates were formed which was observed using transmission electron microscopy and Thioflavin T fluorescence measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 15 publications
(20 reference statements)
2
24
0
Order By: Relevance
“…However, monomers and large peptides have been found in amyloid‐like β‐LG fibrils after microwave heating at 80 °C and pH 2.0 (Hettiarachchi, Melton, Gerrard, & Loveday, ). Fibrils can also be formed at room temperature and pH 2.0 from a peptide mixture obtained by hydrolysis of β‐LG with AspN endoproteinase (Akkermans, Venema, van der Goot, Boom, & van der Linden, ). Ghadami, Khodarahmi, Ghobadi, Ghasemi, and Pirmoradi () suggested that some of the lysine residues in β‐LG are of critical importance in the aggregation process.…”
Section: Bovine Milk Proteinsmentioning
confidence: 99%
“…However, monomers and large peptides have been found in amyloid‐like β‐LG fibrils after microwave heating at 80 °C and pH 2.0 (Hettiarachchi, Melton, Gerrard, & Loveday, ). Fibrils can also be formed at room temperature and pH 2.0 from a peptide mixture obtained by hydrolysis of β‐LG with AspN endoproteinase (Akkermans, Venema, van der Goot, Boom, & van der Linden, ). Ghadami, Khodarahmi, Ghobadi, Ghasemi, and Pirmoradi () suggested that some of the lysine residues in β‐LG are of critical importance in the aggregation process.…”
Section: Bovine Milk Proteinsmentioning
confidence: 99%
“…These can be made by heating an acidic protein or peptide solution under some stirring, which leads to both hydrolysis and fibril assembly at the same time, albeit at a different rate. The fibril length depends on reaction-time and shear rate (Akkermans et al 2008), and they have been used to reinforce microcapsules (Kroes-Nijboer et al 2012, Rossier-Miranda et al 2010. Recently, β-LG fibrils were found not only to provide a more elastic interface compared to native β-LG, but also a better oxidative stability to encapsulated fish oil core (Serfert et al 2014).…”
Section: Biopolymersmentioning
confidence: 99%
“…In that case both gelation and hydrolysis took place at pH 8. Enzymatic hydrolysis was also induced in the case of β -lactoglobulin, but at pH 7, and electron microscopy reveals fi bril formation only after the pH was changed to 2 [20] . Thus, the pH is important in the aggregation and thought to affect the interaction between the according peptides before fi brillization.…”
Section: Protein -Based Fibrilsmentioning
confidence: 99%